A Contactless start of Three Phase Induction Motor amidst Corona Pandemic - Bisht, Tanuj (PREPARE@u® | IEI Conferences, 2021)
The noble corona virus lead to complete shut down of all Industries in India. Production almost came to a halt during the lock down and the Indian economy had to go through tough times. Slowly as the lock down was lifted in stages the biggest challenge that came before the Government was to restart theindustries following the norms of Social Distancing. As we know that three phase Induction motors are the widely used prime movers in Industry because of their robust construction , low maintenance cost and variable speed operation. These motors are installed in almost 90% of industrial processes where there switching is carried out to control different machines in Industries. This switching is based on physical touch with the motor starter. Amidst corona pandemic when the machine operators change their shifts the virus may settle down on the motor starter and this way is likely to spread at a faster rate. In this paper a methodology has been developed to offer contact less start of three Phase Induction Motor to offer both Electrical Fire safety as well as safety against the global corona virus